Lethal Thalassospira povalilytica Sepsis in a Patient With Asplenia: An Alert for Clinicians - Hirokazu Toyoshima; Kohei Unno; Kanako Nakamura; Chiaki Ishiguro; Motoaki Tanigawa; Hirofumi Okuda (Annals of Internal Medicine: Clinical Cases)
In patients with asplenia, Streptococcus pneumoniae is the most common cause of overwhelming sepsis; however, many other pathogens also need to be considered. Thalassospira povalilytica, a marine bacterium, can cause invasive infectious diseases in such patients. Here, we describe the case of a previously healthy 65-year-old man, who presented with a 2-day history of fever and died within 24 hours because of lethal sepsis caused by T povalilytica. This case should alert clinicians regarding the potential of lethal infections caused by T povalilytica.